Pengembangan Media Pembelajaran Berbasis Interactive Flat Panel (IFP) Untuk Meningkatkan Keterampilan Motorik Halus Anak Usia 5-6 Tahun Di TK Negeri Pembina Cibadak Kabupaten Lebak - Aswar Suwartini; Isti Rusdiyani; Tri Sayekti (LPPM Institut Pendidikan Nusantara Global, 2026)
The development of learning media is an important effort to improve the quality of early childhood education, particularly in stimulating children's fine motor skills. This study aims to develop Interactive Flat Panel (IFP)-based learning media and examine its feasibility and effectiveness in improving the fine motor skills of children aged 5-6 years at TK Negeri Pembina Cibadak, Lebak Regency. The study employed a Research and Development (R&D) approach using the ADDIE model, consisting of analysis, design, development, implementation, and evaluation. The data were collected through observation, interviews, expert validation questionnaires, pre-test, post-test, and documentation. The novelty of this study lies in the development of an IFP-based interactive learning medium specifically designed for fine motor stimulation through tracing, puzzle, drag-and-drop, and color-shape activities in early childhood learning. The validation results showed that the media was very feasible, with a material expert score of 90% and a media expert score of 88%. The trial involving 20 children showed an increase in the average fine motor score from 65 in the pre-test to 85 in the post-test, with an N-Gain value of 0.57. These findings indicate that IFP-based learning media is feasible and effective for supporting fine motor development in children aged 5-6 years.